The Effect of Information Presentation Method, Information Kind and the Retention Intervals on the Ability of Recognition and Recall among Yarmouk University Students - Al-Jarrah , Abdelelnaser; AbuAhmad, Maisaa (Jordan Journal of Educational Sciences, 2015)
This study aimed at investigating the effect of information presentation method (story, picture), information kind (typical/ atypical) with the schema, and the retention intervals (1 h, 48 h, and 1 week) on the ability of recognition and recall among Yarmouk university students. The sample of the study consisted of (100) Yarmouk university undergraduate students in the summer term of the academic year 2013/2014. The results of the study revealed that the remembering of atypical actions was better than typical ones, regardless of the test type (recognition, recall), and recognition is better than recall in all retention intervals (1 h, 48 h, and 1 week). The results also revealed that there were statistical significant differences at the level (α=0.05) in recognition and recall due to information presentation method (story, picture), where the recognition and recall levels of actions in the picture were better than those in the story. The results also revealed that when presenting information by story, the recognition of atypical actions was better than typical ones across all retention intervals, while the recall of atypical actions were better than typical ones only at the (1-h) retention interval. At the longer retention intervals, the recall of typical actions was better than atypical ones. However, when presenting information by picture, the recognition of atypical actions was better than typical ones at (1-h) and (48-h), while the recall of atypical actions was better than typical ones across all retention intervals